Mosaic 2 : - Wegmann, Brenda (Tổng hợp Thành phố Hồ Chí Minh : McGraw-Hill, 2007)
Mosaic 2-Reading consist of chapter structure- with consistent part headings, activity, labeling, and clear guidance-strengthens the academic experience: part 1: Reading skills and strategies, part 2: Reading skills and strategies,part 3: Tying it on together